The (ir)relevance of real wage rigidity in the New Keynesian model with search frictions - Michael U. Krause; Thomas A. Lubik (The Johns Hopkins University, Department of Economics, 2003)
We explore the role of real wage dynamics in a New Keynesian business cycle model with search and matching frictions in the labor market. Both job creation and destruction are endogenous. We show that the model generates counterfactual inflation and labor market dynamics. In particular, it fails to generate a Beveridge curve: vacancies and unemployment are positively correlated. Introducing real wage rigidity leads to a negative correlation, and increases the magnitude of labor market flows to more realistic values. However, inflation dynamics are only weakly affected by real wage rigidity. This is because of the presence of labor market frictions, which generate long-run employment relationships. The measure of real marginal cost that is relevant for inflation dynamics via the Phillips curve contains a dynamic component that does not necessarily move with real wages.
Keywords: E24; E32; J64; 330; Labor Market; Real Wage; Search and Matching; New Keynesian Model; Beveridge Curve; Lohnbildung; Lohnrigidität; Neukeynesianische Makroökonomik; Arbeitsmarkt; Friktionelle Arbeitslosigkeit; Theorie